Teasing out the impacts of climate change on agricultural development - Knox, Jerry W.; Kay, Melvyn G. (Ip Publishing, 2010)
plethora of articles, books, and academic papers. Not least are the detailed and extensive publications of the Inter-Governmental Panel on Climate Change (IPCC) which set out in their latest assessment (AR4), the scientific, technical, and socio-economic information relevant for understanding the risks posed by human- induced climate change, and the policy options for dealing with it. Although it is useful to study and identify the specific benefits and risks of a changing climate, in practical terms, the future of the world in which we live will be influenced as much, if not more, by a rich mix of population growth and socio- economic development and fundamentally the need to produce more food with fewer resources. Indeed, these issues are the very reasons why we now have to face a changing climate which will in turn be impacted by it. In 2009, the UK Chief Scientist Professor John Beddington warned that by 2030 global food shortages, scarce water and insufficient energy resources would unleash public unrest, cross-border conflicts and mass migration as people fled the worst-affected regions of the world and sought refuge in ‘safe havens'. This was the so-called 'perfect storm' in which climate change was seen as yet another dark cloud on the horizon. He warned that food reserves were at a 50 year low, but by 2030 we would need 50% more food and 30% more fresh water. "There are dramatic problems out there, particularly with water and food, but energy also, and they are all intimately connected" Beddington said. Other eminent scientists, such as James Lovelock in his book ‘The Final Warning - the vanishing face of Gaia' have similarly urged for a ‘call to arms' to combat climate change and the perils ahead unless we reduce our carbon emissions and control population growth. When Thomas Malthus talked of the inextricable links between food production and population growth in 1798, few people would have thought it possible that his ‘Malthusian curse' could again destabilize society in the 21st Century. Let's hope that climate change will not suffer ‘media malaise' and the urgency to deal with these issues will not be sidelined by short-term priorities for economic regeneration. Whilst we talk a lot about climate change in the developed world, in reality it is in the developing world where the impacts of climate change will be felt most. This is home to millions of the most disadvantaged people who depend on renewable natural resources for their livelihoods. For this reason we asked a number of leading specialists to prepare short but informed insights into the impacts of climate change across a range of natural resources in the context of agricultural development, both in the developed world, and developing world, to provide some comparison of both the issues and priorities. We asked them not to get bogged down in the detail but to draw out the salient issues as they see them. The result is this set of integrated papers which address the subjects of agriculture and food production, forestry, livestock, and the implications for engineering on water security. We hope they provide you with a refreshing perspective on the outlook for agriculture and that you find them both interesting and in